The female body in Roman antiquity: beauties and representational standards in Pompeii parietal paintings - Isbaes, Gabriela (Romanitas - Revista de Estudos Grecolatinos, 2023)
The insertion of the body as an object of investigation in History dates back to the second half of the 20th century, when the dialogues with gender epistemologies were constructed and allowed to think about the different ways that individuals had to subjectify themselves over time. In the case of antiquity, we can access that bodies by the analyzes of archaeological remains, which brings cultural aspects related to the ancients and their bodies. Thus, representations of the female body in the paintings of the Pompeii archaeological site are analyzed. It is intended to understand if these representations indicated an adequacy of women to aesthetic and behavioral standards, or if they can also serve to demonstrate a certain female agency in the control of their bodies, that is, a heterogeneity of conceptions about them, during the Roman imperial period.